Enhanced biomethanization of waste polylactic acid plastic by mild hydrothermal pretreatment: Taguchi orthogonal optimization and kinetics modeling. (1st May 2021) - Mu, Lan; Zhang, Lei; Ma, Jiao; Zhu, Kongyun; Chen, Chuanshuai; Li, Aimin
Highlights: Biodegradation performance of PLA plastic at both AD conditions were investigated. Low hydrolysis rate was identified as the limiting step of PLA degradation in AD. HTT effectively enhanced methane yields of PLA by 1.2–15.3 times. Hydrolysis kinetic of PLA plastic was improved from 0.001 to 0.004–0.111 day −1 . Cleavage of ester linkage was the mechanism of HTT of PLA plastic. Abstract: Polylactic acid (PLA) plastic is becoming a popular alternative to traditional petroleum-based plastics, but the biodegradability in engineered biological system is still a matter of concern. In this study, the biodegradability of PLA plastic at mesophilic and thermophilic AD were investigated, and a hydrothermal pretreatment was proposed to enhance the hydrolysis of PLA plastic and subsequent biomethanization. For raw PLA plastic, the biodegradation results indicated that PLA was hardly biodegraded at mesophilic conditions (only 50.5 ± 0.5 mL/g VS after 146 days). Although it was converted into biogas at thermophilic conditions after long incubation period (442.6 ± 1.1 mL/g VS), the long digestion time (T90 95.8 days) was destined to be infeasible for practical application. In contrast, hydrothermal pretreatment significantly enhanced the hydrolysis rates of PLA plastic in AD process from 0.001 day -1 for raw PLA plastic to 0.004–0.111 day −1 . By balancing biogas production efficiency, energy and reagent cost, the conditions of 200 °C, 10 min and no alkali addition were recommended for hydrothermal pretreatment of waste PLA plastic in practice. At the optimized hydrothermal pretreatment conditions, 460.1 ± 25.0 mL/g VS was achieved in less than 30 days, which was comparable for AD of food waste (FW). Furthermore, LC-QEMS analysis proved that cleavages of ester bonds in PLA and its reaction with water molecule was the mechanism of triggering the hydrothermally decomposition of PLA. These results suggested the PLA-plastic waste co-mingled with OFMSW could be efficiently biomethanized into biogas by involving a mild hydrothermal pretreatment in practical application.